1991
DOI: 10.1136/bmj.302.6786.1178
|View full text |Cite
|
Sign up to set email alerts
|

Importance of maternal history of non-insulin dependent diabetic patients.

Abstract: Objective-To assess the family history ofdiabetes in non-insulin dependent diabetes mellitus with particular emphasis on parental phenotype.Design-Family histories were obtained from an existing computerised database and supplemented by postal questionnaires.Setting-Diabetic service of a provincial teaching hospital.Subjects-A total of 1326 patients with non-insulin dependent diabetes who had been referred to diabetic clinics over the past 10 years and from whom data had been collected for inclusion in the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
94
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(114 citation statements)
references
References 6 publications
18
94
1
1
Order By: Relevance
“…Previous studies in the Pima Indians have shown a much higher prevalence of both type 2 diabetes and obesity in offspring of women who developed diabetes before or during pregnancy than in the offspring of nondiabetic women or the offspring of women who developed diabetes after delivery (prediabetic women) (2,5). This finding is consistent with the greater frequency of diabetes found in offspring of type 2 diabetic mothers than of type 2 diabetic fathers in Pima Indians (2) and in other populations (13,14). These data suggest that exposure to the intrauterine diabetic environment is an important determinant of type 2 diabetes and obesity in adolescence and young adulthood, in addition to the genetic predisposition presumably present in the offspring of both diabetic and prediabetic women (15).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies in the Pima Indians have shown a much higher prevalence of both type 2 diabetes and obesity in offspring of women who developed diabetes before or during pregnancy than in the offspring of nondiabetic women or the offspring of women who developed diabetes after delivery (prediabetic women) (2,5). This finding is consistent with the greater frequency of diabetes found in offspring of type 2 diabetic mothers than of type 2 diabetic fathers in Pima Indians (2) and in other populations (13,14). These data suggest that exposure to the intrauterine diabetic environment is an important determinant of type 2 diabetes and obesity in adolescence and young adulthood, in addition to the genetic predisposition presumably present in the offspring of both diabetic and prediabetic women (15).…”
Section: Discussionsupporting
confidence: 81%
“…We should also note the possible recall bias [12,16,31] in our study. Although we have no relevant data to address this issue, we do not think that our results were affected by recall bias because of the relatively large sample size and the presence of a normal fasting glucose control group.…”
Section: Discussionmentioning
confidence: 76%
“…The existence of excess maternal transmission of type 2 diabetes is still in controversial issues. Although the majority of studies suggest that excess maternal transmission occurs [6,7,[11][12][13][14][15][16][17][18][19], however, a few studies refute this finding [20][21][22]. Recently, the Framingham Offspring Study suggested equivalent maternal and paternal effects on risk for offspring diabetes [20].…”
Section: Introductionmentioning
confidence: 99%
“…NIDDM seems to have a predominant maternal mode of transmission in Caucasians with a relatively low prevalence of the disease [4]. After adjustment for age (mothers live longer than fathers), NIDDM is one-and-a-half times more prevalent in mothers than in fathers of patients with NIDDM in Scandinavia [5].…”
Section: Evidence That Niddm Is An Inherited Diseasementioning
confidence: 99%